2001
DOI: 10.1046/j.1468-1331.2001.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐term functional benefits in children with cerebral palsy treated with botulinum toxin type A: 1‐year follow‐up using gross motor function measure

Abstract: One of the main goals when treating spasticity is to relieve pain and improve function. Intramuscular injection of botulinum toxin type A (BTX-A) has gained widespread acceptance in the treatment of spastic cerebral palsy. Several studies have clearly shown the short-term functional benefit of BTX-A treatment. Information is limited, however, on the efficacy of medium and long-term regimens, using repeated injection of BTX-A. The aim of the present open-label, prospective study was to evaluate functional outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
2
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 34 publications
4
60
2
3
Order By: Relevance
“…10,[33][34][35] The GMFM served well as a measure of foundational skills with magnitudes of change consistent with previous BoNT-A studies. [10][11][12]36 In the associated qualitative component of the study, mothers frequently spontaneously mentioned their child's greater ease and fluidity of movement, straighter posture, and noticeably improved balance during walking and playground activities. In future, it might be useful to employ a measure such as the Gross Motor Performance Measure 37 to assess the impact of reduced spasticity on quality attributes such as stability, coordination, and alignment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…10,[33][34][35] The GMFM served well as a measure of foundational skills with magnitudes of change consistent with previous BoNT-A studies. [10][11][12]36 In the associated qualitative component of the study, mothers frequently spontaneously mentioned their child's greater ease and fluidity of movement, straighter posture, and noticeably improved balance during walking and playground activities. In future, it might be useful to employ a measure such as the Gross Motor Performance Measure 37 to assess the impact of reduced spasticity on quality attributes such as stability, coordination, and alignment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In a randomized controlled trial of botulinum A toxin and orthoses versus best physiotherapy practice, Boyd et al 53 found a dose-response relationship between GMFCS level and GMFM change score. Linder et al 51 reported greater change in children who were younger and were in GMFCS levels less involved than IV. In a pilot study of intensive, intermittent physical therapy, Trahan and Malouin 43 found that children in level IV improved, whereas children in level V did not.…”
Section: Experimental Researchmentioning
confidence: 97%
“…Experimental studies citing the GMFCS have included a range of interventions used in the physical management of children with CP, including physical therapy, [43][44][45][46] recreation, 47 orthoses, 48 selective dorsal rhizotomy, 49 intrathecal baclofen, 50 botulinum A toxin, 51,52 and orthopaedic surgery. 37 In two randomized controlled trials, the GMFCS has been used to overcome bias between treatment groups by stratification before allocation 46 or by comparing treatment groups before analysis.…”
Section: Experimental Researchmentioning
confidence: 99%
“…Foot deformities, congenital · Foot deformities, acquired · Foot deformities, neuromuscular · Club foot · Flatfoot sequenten peritalaren Arthrolyse [21], zu letzt etwas abgemildert durch die operative Vorgehensweise "à la carte" [ [4,19]. Operati ve Maßnahmen kommen praktisch nie zur Anwendung.…”
Section: Introductionunclassified